Homogeneização dos efeitos da paisagem em uma microbacia hidrográfica no sul do Brasil - Medeiros, Gabriela (2022)
Associating anthropogenic effects with biodiversity variation is fundamental to understanding how anthropogenic impacts extrapolate to public supply watersheds. The structure and dynamics of metacommunities in aquatic environments depend not only on the river network but also on many factors. Therefore, we evaluated a watershed used for public supply, considering 1) the reflection of geoenvironmental fragility in water conditions and the concentration of metals in the surface sediment; 2) the association between density and species richness of diatoms, considering local environmental variables, spatial variables, landscape characteristics, and the historical community as driving factors, comparing their possible dispersal routes. Four samplings were carried out, collecting water and surface sediments at eight sampling stations in the watershed of the Cascavel River, Paraná, Brazil. These variables were associated with the environmental fragility resulting from the characteristics of land use and occupation, slope, soil type, and climate of the region. The watershed suffers significant impact from urbanization and agricultural expansion, causing depreciation of riparian vegetation and exposure to erosive conditions. The high agricultural exploitation of the municipality reflects directly on the homogenization of the landscape effects on limnological characteristics and the diatom community. The small scale of the watershed resulted in a slight spatial gradient, reflecting the low variation of community richness among sampling stations. However, temporal heterogeneity associated with rainfall fluctuation throughout the year can cause temporal variation in the relative abundance of species. This pattern results from resource supply that increases biodiversity over time, allowing for the coexistence of species that alternate between dominance and persistence. We demonstrate that predictors of different natures act together to explain diatom communities in micro-watersheds